FOUR MAIN CHARACTERISTICS OF ENGLISH PRAGMATICS - Dey, Manna Dey (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Pragmatics is a linguistic field that explores the complex relationship between language, context, and meaning. It involves analyzing how speakers and writers use language to convey not only literal information, but also social, cultural, and emotional cues that shape communication. Pragmatics examines how language users interpret and infer meaning based on contextual factors such as tone, gesture, and social norms, and how they use language to achieve various goals and outcomes. By uncovering the hidden meanings and intentions behind language use, pragmatics provides valuable insights into human communication and helps us to better understand how language shapes our social interactions and relationships Furthermore, pragmatics plays a crucial role in language learning and teaching, as it helps learners develop their communicative competence and understand the nuances of language use in different contexts. It also has practical applications in fields such as advertising, politics, and law, where the use of language can have significant impacts on audience perceptions and behaviors. Overall, pragmatics is a dynamic and multifaceted field that continues to evolve and shape our understanding of language and communication in diverse contexts.